PEMBUATAN MODEL CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DINAS KESEHATAN DIY MENGGUNAKAN METODE COBIT 4.1 DENGAN DOMAIN DELIVERY AND SUPPORT (DS) - Ali Tarmuji; Ilham Nurfuadi (Telematika, 2015)
The development of health information systems at the Department of Health DIY basically already developed in earlier periods, including the presence of DGS (Digital Government Services), but the ministry has not been able to maximize sample information service on the website Department of Health DIY, it is still not fully known by many society, so the lack of public knowledge about the latest information related to health. stage in this research is the search data by observation, interview, and literature study, analysis of current conditions, SWOT analysis, data analysis includes operational CRM, analytical CRM, collaborative CRM, and the stages of modeling CRM such as the design of the development strategy of services and applications, manufacture of data architecture, application architecture, technology architecture and network infrastructure, and testing models of CRM use due diligence devoted to DIY Health Service and customer satisfaction to the test. Based on the analysis results generated CRM DHO DIY model framework that can provide ease in interacting with customers through the services available.